The Effectiveness of the Problem-Based Learning Method in Civics Learning in Elementary Madrasahs on Students' Critical Thinking Skills and National Attitudes - Silfianti, Silfianti; Ananda, Pramudia (Yayasan Zia Salsabila, 2023)
The issue of low critical thinking skills and weak internalization of national values among Madrasah Ibtidaiyah students has become a serious challenge in Civics Education (PKN) learning. This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) method assisted by Artificial Intelligence (AI) media in improving students’ critical thinking skills and national attitudes at Madrasah Ibtidaiyah in Kendari City. Employing a descriptive qualitative approach, this research involved Civics teachers and fifth-grade students as key informants. Data were collected through observation, in-depth interviews, and documentation, then analyzed using N-Vivo software. The findings indicate that the integration of AI-based media in PBL significantly enhances students' abilities in analyzing civic issues, developing creative solutions, and communicating ideas both verbally and non-verbally more effectively. Furthermore, national values such as tolerance, deliberation, and patriotism were well internalized through problem-based learning activities. This study contributes to the development of constructivist learning theories and offers an innovative instructional model for character education in madrasahs. The model is recommended for broader implementation in primary education curricula based on national values.